A facile synthesis of deuterium labeled 2, 2‐dimethyl‐[2H6]‐succinic acid and its anhydride. (12th March 2013) - Srinivas, G.; Unny, V. K. P.; Mukkanti, K.; Choudary, B. M.
Abstract : Deuterium labeled 2, 2‐dimethyl‐[ 2 H6 ]‐succinic anhydride by a sequence of reactions involving Knoevenagel condensation of [ 2 H6 ]‐acetone with ethyl cyanoacetate in the presence of piperidine, Michael addition of cyanide, HCl hydrolysis, simultaneous decarboxylation, and subsequent dehydration using acetic anhydride in an overall yield of 34.23% based on [ 2 H6 ]‐acetone utilized in the reaction is reported. The title compounds were characterized and confirmed spectroscopically by Fourier transform infrared, 1 H‐NMR, and Mass. The chemical purity as determined by HPLC was 99%. To the best of our knowledge, the synthesis of these specifically deuterium labeled compounds has not been reported so far. Abstract : A facile synthesis of deuterium labeled 2, 2‐dimethyl‐[ 2 H6 ]‐succinic acid and its anhydride by a sequence of reactions involving Knoevenagel condensation of [ 2 H6 ]‐acetone with ethyl cyanoacetate in the presence of piperidine, Michael addition of cyanide, HCl hydrolysis, simultaneous decarboxylation, and subsequent dehydration using acetic anhydride in an overall yield of 34.23% on the basis of [ 2 H6 ]‐acetone utilized in the reaction is reported.